Tracing the mutated HTT and haplotype of the African ancestor who spread Huntington disease into the Middle East - Squitieri, Ferdinando; Mazza, Tommaso; Maffi, Sabrina; De Luca, Alessandro; AlSalmi, Qasem; AlHarasi, Salma; Collins, Jennifer A.; Kay, Chris; Baine-Savanhu, Fiona; Landwhermeyer, Bernard G.; Sabatini, Umberto; Hayden, Michael R. (Genetics in medicine, 2020)
Purpose We aimed to determine the origin and genetic characteristics of Huntington disease (HD) in the Middle East. Methods We performed genetic and genealogical analyses to establish the ancestral origin of the HTT pathgenic variant from a large kindred from Oman (hereafter called the OM-HD-01 pedigree) by single-nucleotide polymorphism and dense haplotype analysis genotyping. Results We traced the oldest ancestry of the largest, eight-generation, OM-HD-01 pedigree ( n = 302 subjects, with 54 showing manifest HD) back to sub-Saharan Africa and identified a unique HD haplotype carried by all pedigree members, which consisted of portions of the C6 and C9 haplotypes and was carried by all affected members. Such a unique HD haplotype was of African origin and appeared to be associated with large CAG repeat expansions on average and high frequency of juvenile-onset HD. Three other families from the same area were also identified and found carrying a Caucasian HD haplotype A, also shared by most families of Arab ancestry. Conclusion Mutated HTT spread into Middle East with a unique haplotype of African origin, appeared to be associated with juvenile-onset, a HD condition frequently occurring in Black Africans, and may have a significant impact on further development of novel targeted genetic therapies.